OPTIMIZING THE ROLE AND INNOVATION OF GEN Z IN FACING OPPORTUNITIES AND CHALLANGES IN LEARNING ENGLISH THROUGH SOCIAL MEDIA - Jawa Dwipa, Ahya Satriya; Abas, Totoh Tauhidin (Jurnal Education and Development, 2025)
The 21st century is marked by rapid technological developments and globalization, which have had a significant impact on various aspects of life, including education. Generation Z, as a digital generation born and raised amidst technological advancements, faces various opportunities and challenges in the learning process, particularly in English language learning. Social media has become one of the platforms most frequently used by Generation Z, not only for entertainment but also as a learning support tool. This research used a descriptive qualitative approach with data collection methods using questionnaires and observations. The sample in this study was Generation Z students studying English. Data analysis was conducted using a thematic approach to identify patterns of social media use and innovations emerging in the learning process. The research findings show that although Generation Z faces challenges such as language interference and digital distractions, they are also able to utilize social media creatively and innovatively to improve their English skills, particularly in vocabulary, pronunciation, and writing. Social media also opens up opportunities for more flexible collaborative and self-taught learning. The study's conclusions confirm that social media can be optimized as an effective learning tool for Generation Z in facing the challenges of the digital era. The active role of teachers and educators remains crucial in guiding, directing, and developing critical and responsible learning characteristics.